2020
DOI: 10.1073/pnas.1918682117
|View full text |Cite|
|
Sign up to set email alerts
|

Loss of nucleus accumbens low-frequency fluctuations is a signature of chronic pain

Abstract: Chronic pain is a highly prevalent disease with poorly understood pathophysiology. In particular, the brain mechanisms mediating the transition from acute to chronic pain remain largely unknown. Here, we identify a subcortical signature of back pain. Specifically, subacute back pain patients who are at risk for developing chronic pain exhibit a smaller nucleus accumbens volume, which persists in the chronic phase, compared to healthy controls. The smaller accumbens volume was also observed in a separate cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
61
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 85 publications
6
61
0
Order By: Relevance
“…Using resting-state functional magnetic resonance imaging (fMRI), highly similar frequency-dependent changes have been reported in multiple chronic pain conditions. In trigeminal neuralgia [ 52 ], postherpetic neuralgia [ 12 ], and chronic back pain [ 28 , 51 ] populations, a loss of slow-5 power was not only noted in prefrontal cortex [ 52 ] but also in subcortical regions such as the nucleus accumbens, which share projections with sub-regions of the frontal cortex areas amongst other (meso-)limbic structures. Thus, in general, the suppression of the frontal cortex (potentially along the frontostriatal pathway) low-frequency oscillation in the slow-5 sub-band may represent a maladaptive cortical process that is derived from persistent pain or mechanisms that sustain a pain state.…”
Section: Discussionmentioning
confidence: 99%
“…Using resting-state functional magnetic resonance imaging (fMRI), highly similar frequency-dependent changes have been reported in multiple chronic pain conditions. In trigeminal neuralgia [ 52 ], postherpetic neuralgia [ 12 ], and chronic back pain [ 28 , 51 ] populations, a loss of slow-5 power was not only noted in prefrontal cortex [ 52 ] but also in subcortical regions such as the nucleus accumbens, which share projections with sub-regions of the frontal cortex areas amongst other (meso-)limbic structures. Thus, in general, the suppression of the frontal cortex (potentially along the frontostriatal pathway) low-frequency oscillation in the slow-5 sub-band may represent a maladaptive cortical process that is derived from persistent pain or mechanisms that sustain a pain state.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the abnormal FC between the hypothalamus and the midbrain dopaminergic system (in particular the ventral tegmental area) in chronic CH patients ( 18 ) suggests that the possible pathways of chronicization pass through the mesocorticolimbic system also in CH. It is now accepted that the midbrain dopaminergic system is also stimulated by aversive stimuli such as pain ( 61 ), and the nucleus accumbens, a key component of the mesocorticolimbic system receiving direct projections from the ventral tegmental area, seems to be involved in the chronicization of pain in humans ( 62 64 ). This possibility in CH is also fostered by the recent proposal of the ventral tegmental area as the main target of DBS ( 65 ) and by the observation that long-term DBS can revert chronic to episodic CH ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that the volume of the nucleus accumbens was signi cantly decreased in the ONFH patients compared with the healthy controls. Makary MM et al 42 provided evidence that a lower nucleus accumbens volume confers risk for developing chronic pain and that altered nucleus accumbens activity is a signature of the state of chronic pain.…”
Section: Discussionmentioning
confidence: 99%